Gardnerella subgroup dominant microbiomes are associated with divergent cervicovaginal immune responses in a longitudinal cohort of Kenyan women - Shvartsman, Elinor; Perciani, Catia T.; Richmond, Meika E. I.; Russell, Justen N. H.; Tough, Riley H.; Vancuren, Sarah J.; Hill, Janet E.; KAVI-ICR,; Jaoko, Walter; McKinnon, Lyle R.; Sandstrom, Paul A.; MacDonald, Kelly S. (Frontiers in Immunology, 2023)
Most cervicovaginal microbiome-immunology studies to date have relied on 16S rDNA microbial profiling which does not resolve the molecular subgroups of Gardnerella, believed to be central to the pathogenesis of bacterial vaginosis (BV) and subsequent risk of HIV acquisition. Here we used the cpn60 universal target which in addition to other microbial taxa, resolves four Gardnerella subgroups, for cervicovaginal microbial profiling in a longitudinal cohort of Kenyan women to examine associations with cellular and soluble markers of HIV susceptibility. Participants (N = 41) were sampled, contributing 362 samples for microbiome analysis. All non-Lactobacillus dominant microbial communities were associated with high pro-inflammatory cytokine levels. Divergent associations were observed among different Gardnerella subgroup dominated communities with respect to the chemokine IP-10. Specifically, Gardnerella subgroup A dominant and polymicrobial communities were associated with reduced concentrations of IP-10 in adjusted linear mixed models (p<0.0001), compared to microbial communities dominated by Lactobacillus (non-iners) species. However, these associations did not translate to significant differences in the proportion or absolute number of CCR5, HLA-DR and CD38 expressed on cervical CD4+ cells. These findings suggest that some associations between Gardnerella subgroup dominant microbiomes and mucosal immunity differ and are relevant for the study of BV-pathogenesis and understanding the mechanisms of BV-associated HIV risk.